Effect of social capital on women microenterprise performance in Kelantan : a conceptual framework - Isidore Ekpe; Norsiah Mat; Abdullah Al- Mamun (Faculty of Entrepreneurship and Business,UMK, 2015)
This study is aimed at determining the influence of social capital on women micro- enterprise performance in Kelantan State of Malaysia, so as to enable Malaysian government determine what area to focus in redesigning enterprise development programs, and what strategies to develop in enhancing the ability of women entrepreneurs to benefit from their social capital and improve business performance. Also, the moderating effect of attitude on the relationship between social capital and women micro-enterprise’s performance is assessed. The study employs a cross- sectional survey design, with simple random sampling, to collect data from 385 women entrepreneurs in Kelantan (women entrepreneurs who belonged to any loan group and those who did not). Descriptive statistics and hierarchical regression will be used to analyze data.